Decolonizing Evaluation of Indigenous Land-Based Programs: A Settler Perspective on What We Can Learn from the LANDBACK Movement - Deborah DeLancey (The Evaluation Center at Western Michigan University, 2023)
There is increasing recognition of the importance of land-based programming in promoting Indigenous cultural resurgence and community-building. This article explores the challenges associated with evaluation of on the land programs, and considers ontological and epistemological challenges associated with applying a postpositivist western evaluation approach. It is suggested that Indigenous-led evaluation should be mandated for Indigenous land-based programs, consistent with emerging recognition of Indigenous peoples' rights to sovereignty over programs and services.